ANALYSIS OF EFFECTIVENESS, TRANSPARENCY AND ACCOUNTABILITY OF ZAKAT MANAGEMENT AT THE NATIONAL ZAKAT AMIL AGENCY OF BONDOWOSO REGENCY - MAHENDRATA, GENTA; NASTITI, ARI SITA; KAMELIA FIEL AFROH, IBNA (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to analyze the effectiveness, transparency, and accountability of zakat management at the National Amil Zakat Agency (BAZNAS) of Bondowoso Regency. Zakat plays a strategic role in promoting social justice and empowering the Muslim community economically. Therefore, zakat governance must align with Islamic principles and financial reporting standards, such as PSAK 109. This research adopts a descriptive qualitative approach, using data collection methods such as observation, in-depth interviews, and documentation. Data validity was ensured through triangulation techniques. The findings reveal that in terms of effectiveness, BAZNAS Bondowoso has successfully collected zakat from the formal sector (eg, civil servants), although it has not yet optimized collection from the informal sector. Regarding transparency, BAZNAS regularly publishes general financial reports; However, a digital system that allows individual zakat contributors to track their donations in real-time is still lacking. Accountability is relatively well-maintained through quarterly financial reporting, internal verification, external audits, and supervision by the Sharia Supervisory Board (DPS). Nevertheless, several PSAK 109 elements—such as the Notes to Financial Statements (CaLK) and disclosure of accounting policies—have not been fully implemented. This study recommends the development of a digital reporting system, expansion of zakat contributor bases in the informal sector, and enhancement of monitoring and mentoring for productive zakat programs. These steps are expected to improve the overall effectiveness, transparency, and accountability of zakat management.